Beschäftigungseffekte ausgewählter Maßnahmen der beruflichen Weiterbildung in Deutschland: eine Bestandsaufnahme - Martin Biewen; Bernd Fitzenberger; Aderonke Osikominu; Robert Völter; Marie Waller (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– New administrative data have recently permitted a differentiated and dynamic evaluation of the employment effects of measures of further vocational training in Germany which have been conducted in the context of active labour market policy. The data available for this purpose include firstly data for the time of the Employment Promotion Act in the 1980s and 1990s, and secondly the data of the Integrated Employment Biographies (Integrierten Erwerbsbiografien (IEB)) for the Social Code III from the year 2000 onwards. The aim of this paper is to assess the results of currently presented evaluations on the basis of these new data sets. We report results from other studies as well as those from our own studies. The results show that the employment effects of measures of further vocational training are far more positive than suggested by studies conducted in the past on the basis of survey data. It can be seen however, that long training measures often do not show their positive effects until some years later. This requires panel data over a long period of time, which are currently only available for the 1980s and 1990s. For this reason, policy implications about the effectiveness of further training measures should not be drawn on the basis of short-term employment effects alone.
Keywords: 330; Weiterbildungsförderung; Beschäftigungseffekte; arbeitsmarktpolitische Maßnahme - Erfolgskontrolle; Trainingsmaßnahme; geschlechtsspezifische Faktoren; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland